A novel chromatin-remodeling complex variant, dcPBAF, is involved in maintaining transcription in differentiated neurons - Soshnikova, Nataliya V.; Azieva, Asya M.; Klimenko, Nataliya S.; Khamidullina, Alvina I.; Feoktistov, Alexey V.; Sheynov, Andrey A.; Brechalov, Alexander V.; Tatarskiy, Victor V.; Georgieva, Sofia G. (Frontiers in Cell and Developmental Biology, 2023)
The PBAF chromatin-remodeling complex is essential for transcription in mammalian cells.Here we describe a novel variant of the PBAF complex from differentiated neuronal cells, called dcPBAF that differs from the canonical PBAF existing in proliferating neuroblasts. We describe that in differentiated adult neurons a specific subunit of PBAF, PHF10, is replaced by a PHF10 isoform that is lacking N-terminal and C-terminal domains (called PHF10D). In addition, dcPBAF does not contain the canonical BRD7 subunit. DcPBAF binds promoters of the actively transcribed neuron-specific and housekeeping genes in terminally differentiated neurons of adult mice. Furthermore, in differentiated human neuronal cells the PHF10D-containing dcPBAF maintains a high transcriptional level at several neuron-specific genes.